PENGARUH KEPEMIMPINAN, DISIPLIN DAN KEPUASAN KERJA TERHADAP KINERJA GURU DI SMK NEGERI JAKARTA - Murrianto; Robi Wijaya (Pasca Sarjana Universitas Satya Negara Indonesia, 2017)
The influence of leadership, job satisfaction and performance Disciplines teacher in SMK Negeri Jakarta. In this study method survey method is used to select the samples randomly from 150 teachers SMK Negeri Jakarta. This study uses the techniques collection is done by making a good questionnaire for a free variable or variable instruments attached. The instrument was tested using the test validity is calculated using SPSS application 16 version softwere through comparison of r and r count table, while for reliability test instrument is calculated by using the formula alpha cron bach. Hypothesis testing in this study using a simple linear regression techniques, correlation of pearson and regression. Resulting in some important points are: 1. There is a relationship between leadership performance. 2. There is a relationship between the disciplines with the performance of teachers. 3. There is a relationship between job satisfaction with the performance of teachers. 4. There is a relationship between the disciplines with the leadership.